Online education adoption in Spain 2008-2019. Drivers and impediments - Rafael López; Ángel Valarezo; Teodosio Pérez-Amaral (International Telecommunications Society (ITS), 2021)
Online learning and training are gaining momentum worldwide by reducing the temporal and spatial limitations associated with the traditional form of face-to-face education. Online education improves access to education and training, especially during the present Covid-19 pandemic. This article focuses on online education adoption in Spain. A large and representative panel database from the ICT in the household's survey by the National Institute of Statistics is used. The first objective is to provide an econometric model for the adoption of online education. Next is to measure the effects of relevant observable individual socioeconomic variables on adoption. A Heckman selection model using panel data for 2008-2019 allows estimating the impact of differences in gender, age, education, digital skills, habitat and income. The drivers and impediments have the expected signs and plausible sizes. The paper concludes with policy recommendations and suggestions for further research.
Keywords: 330